The Malays their problems and future - Syed Husin Ali (The Other Press, 2008)
The Malays as an ethnic group has been defined on the basis of both legal-constitutional and historical-cultural factors. While it is difficult to speculate or visualise correctly the future of any country or people, it is possible to provide a general outline of the trends of the past and present, and probably attempt to at least indicate what should be avoided and promoted to ensure a better future. This is what Dr Syed Husin Ali attempts in this book. In nine chapters, he discusses the Malays and their origin, history, religion, economy, politics and development up to the present day. He connects all of these to the various changes in the forms of modernisation and development programmes which affected, and continue to impact upon, the Malays. Three decades have passed since the book was first published. During that time many changes have taken place in the country. But the basic problems facing the Malays, contends the writer, have remained the same. The current controversies on the declining power of the Malays, as perceived by some, affirm these problems, and make the book more relevant.